TRANSFORMATIONAL LEADERSHIP OF PESANTREN TAHFIZD DARUL QURAN SURAKARTA LEADERS IN STRENGTHENING THE RELIGIOUS CHARACTER OF SANTRIWATI - Zainab Alqudsi; Sofyan Anif; Achmad Fathoni; Ahmad Muhibbin; Sigit Haryanto (IAIN Manado, 2023)
Abstract: Education at Islamic boarding schools not only functions as a transfer of religious knowledge, but also as a place for the formation of religious character. The transformational leadership of Islamic boarding school leaders plays a central role in the process of producing a generation that combines academic skills with strong moral and spiritual character. Transformational leadership does not only involve managerial aspects, but also focuses on building female students' character, morality and spirituality. This research aims to explore and understand the positive impact of transformational leadership of Islamic boarding school leaders in forming a religious generation at the Tahfizh Daarul Qur'an Islamic Boarding School, Surakarta. This research method uses descriptive qualitative. This research found that the transformational leadership of Islamic boarding school leaders in the idealized influence dimension in strengthening the religious character of female students was carried out with the strategy of nurturing with the heart and educating by example, holding muhadharah activities with the aim of forming the character of female students, memorizing the Qur'an which would then be carried out by reciting the Qur'an. an, providing formal education based on science and technology.Key Words : Transformational Leadership, Islamic Boarding School Leader, ReligiousAbstrak: Pendidikan di pesantren tidak hanya berfungsi sebagai transfer ilmu agama, tetapi juga sebagai tempat pembentukan karakter religius. Kepemimpinan transformasional pimpinan pesantren memainkan peran sentral dalam proses mencetak generasi yang memadukan kecakapan akademis dengan karakter moral dan spiritual yang kuat. Kepemimpinan transformasional tidak hanya melibatkan aspek manajerial, tetapi juga berfokus pada pembentukan karakter, moralitas, dan spiritualitas santriwati. Penelitian ini bertujuan untuk mengeksplorasi dan memahami dampak positif kepemimpinan transformasional pimpinan pesantren dalam membentuk generasi religius di Pesantren Tahfizh Daarul Qur’an Surakarta. Metode penelitian ini menggunakan kualitatif deskriptif. Penelitian ini mendapatkan hasil bahwa kepemimpinan transformasional pimpinan pesantren dalam dimensi idealized influence dalam menguatkan karakter religius santriwati dilakukan dengan strategi mengasuh dengan hati dan mendidik dengan keteladanan, mengadakan kegiatan muhadharah dengan tujuan untuk membentuk karakter santriwati, hafal Qur’an yang selanjutnya akan dilakukan khatmil Qur’an, pemberian pendidikan formal berbasis sains dan teknologi.Kata Kunci : Kepemimpinan Transformasional, Pimpinan Pesantren, Religius